Utilization of agency nursing staff in U.S. nursing homes: Trends and insights - Rohit Pradhan; Akbar Ghiasi; Ganisher Davlyatov; Robert Weech-Maldonado (Heliyon, 2025)
This study investigated the trends in agency nursing staff utilization in United States nursing homes against the backdrop of longstanding staffing challenges exacerbated by the COVID-19 pandemic. It analyzed data from the Centers for Medicare and Medicaid Services Payroll-Based Journal (PBJ), LTCFocus.org, Area Health Resources Files, and Rural-Urban Commuting Area codes covering 80,244 nursing home-year observations (2017–2022). Joinpoint regression analysis revealed that agency labor utilization increased across all nursing staff categories (registered nurses, licensed practical nurses, certified nursing assistants), with a significant upward shift beginning in 2020, coinciding with the onset of the COVID-19 pandemic. The study also noted an interesting pattern of increased agency nursing staff use during weekends, possibly due to reduced availability of full-time staff. Ownership analysis revealed that not-for-profit chain facilities had the highest use of agency labor. We also examined differences in agency nursing staff utilization by nursing home size and location (urban/rural). Additionally, state-level variations in agency staff utilization were noted, highlighting regional differences in reliance on agency labor. Additional research is needed to evaluate the policy and operational implications of agency nursing staff utilization in nursing homes.